Observations of changes in acoustic emission waveform for varying seeded defect sizes in a rolling element bearing - Al-Dossary, Saad; Hamzah, R. I. R.; Mba, David (Elsevier Science B.V., Amsterdam., 2009)
The investigation reported in this paper was centered on the application of the acoustic emissions (AE) technology for characterising the defect sizes on a radially loaded bearing. An experimental test-rig was designed such that defects of varying sizes could be seeded onto the outer and inner races of a test bearing. The aim of this investigation was to correlate defect size with specific AE parameters and to ascertain the relationship between the duration of AE transient bursts associated with seeded defects to the actual geometric size of the defect. In addition, the use of AE to detect inner race defects was explored particularly as this known to be fraught with difficulty. It is concluded that the geometric defect size of outer race defects can be determined from the AE waveform.
Keywords: Acoustic emissions Bearing defect size Bearing fault diagnosis Condition monitoring